2013
DOI: 10.1136/bmjopen-2013-003684
|View full text |Cite
|
Sign up to set email alerts
|

Which factors influence decisions to transfer and treat patients with acute intracerebral haemorrhage and which are associated with prognosis? A retrospective cohort study

Abstract: ObjectivesTo identify factors associated with the decision to transfer and/or operate on patients with intracerebral haemorrhage (ICH) at a UK regional neurosurgical centre and test whether these decisions were associated with patient survival.DesignRetrospective cohort study.Setting14 acute and specialist hospitals served by the neurosurgical unit at Salford Royal NHS Foundation Trust, Salford, UK.ParticipantsAll patients referred acutely to neurosurgery from January 2008 to October 2010.Outcome measuresPrima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…A previous UK study found that patients admitted to neurosurgery tended to have larger hematomas, but were younger with better premorbid health. 13 Exclusion of such patients may introduce ascertainment bias. However, given that ICH accounts for over 10% of our stroke population we believe that the great majority of ICHs presenting to hospital have been captured in SSNAP.…”
Section: Discussionmentioning
confidence: 99%
“…A previous UK study found that patients admitted to neurosurgery tended to have larger hematomas, but were younger with better premorbid health. 13 Exclusion of such patients may introduce ascertainment bias. However, given that ICH accounts for over 10% of our stroke population we believe that the great majority of ICHs presenting to hospital have been captured in SSNAP.…”
Section: Discussionmentioning
confidence: 99%
“…We confirmed previous studies suggesting men suffered more often from deep ICH 12 and women were on average older than men. 13 As both age and IVH are established parameters affecting outcome, 14 it is notable that a careful statistical approach accounting for these prognostic factors has not been undertaken in previous observational studies. 3,4 When analyzing outcome, it is important to control for do not treat orders.…”
Section: Discussionmentioning
confidence: 99%
“…Even if patients did not receive surgical intervention, high risk cases require management at a neurosurgical center for neuro-critical care monitoring, especially subarachnoid and subdural hemorrhage. There is also evidence to suggest that hemorrhage cases have better outcomes at neurosurgical centers, regardless of whether surgery was performed [34] .…”
Section: Benefits For Hemorrhagic Strokementioning
confidence: 99%